The Sustainability of Entrepreneurship within the Social and Solidarity Economy: An Analysis of Social Factors - González, Arturo Luque; Benavides, Paul Renato Solís; Sislema, Maria Bertha Aragadovay (Calitatea Vieții, 2020)
The present study is situated within the Ecuadorian social and solidarity economy. It is a diagnosis of the perception of how social factors influence the sustainability of the sector’s entrepreneurship. The perspective presented here is a result of the pragmatism of the civil service of the National Institute of Social and Solidarity Economy and may be taken as a theoretical basis for the design and implementation of comprehensive institutional interventions at the national level. Based on the findings of this study, there is a need to modify the current paradigm of action in the implementation of programs and projects, and to re-assess the reality in which the sector operates at ground level, and the impact of social factors that are part of this ecosystem. A reflection on the successful components, limitations and operational considerations gives insight into the way forward for this sector, and provides guidance on establishing processes of participation, social equity, and economic and social inclusion. The outcome of the research is an innovative instrument that may be used to provide relevant information and references as well as orientation for further research into socially sustainable good practice.